Employment of Cannabis sativa biochar to improve soil nutrient pool and metal immobilization - Anjum, Zufishan; Min, Qi; Riaz, Luqman; Waqar-Un-Nisa,; Qadeer, Samia; Saleem, Aansa Rukya (Frontiers in Environmental Science, 2022)
Soil pollution with heavy metals has become a global issue as a consequence of anthropogenic activities causing gradual loss of soil nutrients and fertility, thus reducing agricultural production. Biochar is recommended as organic and environmental friendly option to address the issue of nutrient deficiency and heavy metal pollution. The present study was performed with biochar derived from Cannabis sativa to surplus soil nutrient pool and heavy metal immobilization. The characterization through Scanning Electron Microscopy (SEM) revealed that biochar was brittle, porous, alkaline and labile in nature. The elemental composition of biochar was carbon (75.3%), oxygen (19.2%), calcium (3.9%), potassium (1.5%) and chlorine (0.08%) determined by Energy Dispersive X-ray Spectroscopy. Fourier transform infrared (FTIR) spectroscopy revealed the occurrence of carbonyl group, phenols, and alcohols in biochar derived from Cannabis sativa. The soil was spiked with Lead and Cadmium salt solution (25 ppm and 250) and incubated for 30 days. It was found that biochar amendments (1% = BC1) and (5% = BC5) significantly (p < 0.05) increased the soil physicochemical properties such as pH, electrical conductivity (EC), oxidizable organic carbon (OC), total organic carbon (TOC) and organic matter (OM). In the case of BC5, OC increased by 189.86%, TOC increased by 189.13%, and OM increased by 188.68% as compared to the control. Similarly, available soil nitrogen (SAN) and soil available phosphorous (SAP) improved by 233.3% and 101.79% respectively compared to control. On the other hand, BC1 showed a significant reduction (p < 0.05) in lead and cadmium concentrations by 45.74% and 56.58% respectively in comparison to BC5 and control. In conclusion, we suggest that Cannabis sativa biochar may serve as an effective treatment for enhancing soil fertility and remediation of soil polluted with heavy metals.